Cross‐Talk Between Ionic and Nanoribbon Current Signals in Graphene Nanoribbon‐Nanopore Sensors for Single‐Molecule Detection. Issue 47 (26th October 2015) - Puster, Matthew; Balan, Adrian; Rodríguez‐Manzo, Julio A.; Danda, Gopinath; Ahn, Jae‐Hyuk; Parkin, William; Drndić, Marija
Abstract : Nanopores are now being used not only as an ionic current sensor but also as a means to localize molecules near alternative sensors with higher sensitivity and/or selectivity. One example is a solid‐state nanopore embedded in a graphene nanoribbon (GNR) transistor. Such a device possesses the high conductivity needed for higher bandwidth measurements and, because of its single‐atomic‐layer thickness, can improve the spatial resolution of the measurement. Here measurements of ionic current through the nanopore are shown during double‐stranded DNA (dsDNA) translocation, along with the simultaneous response of the neighboring GNR due to changes in the surrounding electric potential. Cross‐talk originating from capacitive coupling between the two measurement channels is observed, resulting in a transient response in the GNR during DNA translocation; however, a modulation in device conductivity is not observed via an electric‐field‐effect response during DNA translocation. A field‐effect response would scale with GNR source–drain voltage ( V ds ), whereas the capacitive coupling does not scale with V ds . In order to take advantage of the high bandwidth potential of such sensors, the field‐effect response must be enhanced. Potential field calculations are presented to outline a phase diagram for detection within the device parameter space, charting a roadmap for future optimization of such devices. Abstract : Graphene nanoribbon sensors show a response to single DNA molecules flowing through a nanopore. The response is based on capacitively coupled cross‐talk between the ionic and graphene measurement channels. Circuit simulations show the variety of signals which may be observed, and potential field calculations identify parameters that can enhance detection based on a field‐effect device response.